Increase of Coriander Yield by Using Bio-Extract from Sensitive Plant - Chutichudet, Prasit; Chutichudet, Benjawan (Naresuan University Journal: Science and Technology (NUJST), 2021)
Bio-extract from sensitive plant has been shown to be beneficial for the growth of several vegetables.  In this study, the effects of bio-extract from sensitive plant on fresh weight of coriander were determined under field conditions. The experiments were carried out by diluting the bio-extract from sensitive plant with water at the concentrations of 1:50, 1:100, 1:500 and 1:1,000 and then applied to the coriander in a completely randomized design with four replications, ten plants per replication.  Five hundred milliliters of bio-extract were applied to coriander plants every six days for five times. The experiments were conducted from August 2019 to May 2020 at the agricultural field station of the Department of Agricultural Technology, Mahasarakham University. After planting, the analyzed data of bio-extract results showed that diluted bio-extract at the concentration of 1:50 could increase the contents of nitrogen and potassium in soil when compared to the control (no added of bio-extract). In addition, the levels of pH and EC in soil treated with diluted bio-extract were significantly lower ( p < 0.01) than the control. Also, the coriander plants that were treated with diluted bio-extract at the concentration of 1:500 were found to have the maximal fresh weight of 20.55 g per plant at 45 days after planting. This study therefore suggested that the bio-extract from sensitive plant could be beneficial effect for increasing the yield of coriander. Keywords: Coriander, Bio-extract, Sensitive plant, coriander, organic matter